2002
DOI: 10.1002/etc.5620210708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adsorption to elemental iron on the transformation of 2,4,6‐trinitrotoluene and hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine in solution

Abstract: Abstract-The effect of adsorption to elemental iron on the reductive transformation of 2,4,6-trinitrotoluene (TNT) and hexahydro-1,3,5-trinitro-1,3,5-triazine (royal demolition explosive [RDX]) in aqueous solution was studied with scrap iron and high-purity iron. In batch experiments with the same total iron surface area and a mixing rate of 100 rpm, TNT and RDX were removed from the solution within 30 min. With high-purity iron, adsorbed TNT was reduced to 2,4,6-triaminotoluene (TAT) rapidly, with little accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…6 Effects of Na 2 CO 3 on 2,4-DNT reduction (a), pH variation profiles (b), the reduction products and mass balance (c) and the repeated use of CMCI (d, e) at 100 mg L −1 of 2,4-DNT, pH 7, 0.25 % mass ratio (Cu:Fe), and 200 g L −1 scrap cast iron the iron surface. Similar results (Oh et al 2002) are also reported for the reduction of 2,4,6-trinitrotoluene with highpurity iron, in which the adsorption of dinitro and mononitro intermediates are minimal throughout the reaction. Therefore, the formation of precipitates can be a potential mechanism of CO 3 2− , in which the products of reduction are strongly adsorbed, thereby decreasing the observed efficiency in the current study.…”
Section: Effects Of Operational Parameterssupporting
confidence: 84%
“…6 Effects of Na 2 CO 3 on 2,4-DNT reduction (a), pH variation profiles (b), the reduction products and mass balance (c) and the repeated use of CMCI (d, e) at 100 mg L −1 of 2,4-DNT, pH 7, 0.25 % mass ratio (Cu:Fe), and 200 g L −1 scrap cast iron the iron surface. Similar results (Oh et al 2002) are also reported for the reduction of 2,4,6-trinitrotoluene with highpurity iron, in which the adsorption of dinitro and mononitro intermediates are minimal throughout the reaction. Therefore, the formation of precipitates can be a potential mechanism of CO 3 2− , in which the products of reduction are strongly adsorbed, thereby decreasing the observed efficiency in the current study.…”
Section: Effects Of Operational Parameterssupporting
confidence: 84%
“…Results indicate that there may be impedance to further 2ADNT degradation at this site, with preferential onward reaction of 4ADNT to form 2,4DANT. A similar product distribution was reported by Oh et al (2002) for reductive transformation experiments involving scrap iron, which they described as having high carbon content.…”
Section: Microcosm Testssupporting
confidence: 67%
“…Sustainable biogeochemical cycles have been postulated for abiotic degradation involving iron (Hofstetter et al, 1999), suggesting ferrous-ferric iron cycling would be inexhaustible under highly reducing conditions; however, given the close proximity of results we cannot make any definitive suggestions on specific abiotic transformation mechanisms operative at the study area. Referring back to the concurrent Fe, TNT and TP contaminant peak discussed in the source zone characterization section, it has been commonly reported in laboratory studies that an increased elemental iron or Fe(II) content correlates to increased TNT transformation Downloaded by [University of Connecticut] at 09:58 09 October 2014 rates via direct enhancement of abiotic transformation, where Fe acts as an electron donor in ferrous-ferric iron cycling (Hofstetter et al, 1999;Oh et al, 2002;Hofstetter et al, 2003). Abiotic testwork indicates, however, that transformation rates are low at the study sites, reiterating that the observed product distribution is more likely a function of mobility.…”
Section: Microcosm Testsmentioning
confidence: 98%
See 1 more Smart Citation
“…More than 95 % of the 14 C lost, however, was recovered from the Fe 0 surface through a series of extraction and oxidation procedures. Oh et al [352] treated RDX with scrap iron and high-purity iron under anaerobic conditions. They observed that RDX was readily transformed by both iron sources with no appreciable build-up of identifiable degradates.…”
Section: Chemical Reduction Using Zero-valent Iron (Fe 0 ) Ferrous Imentioning
confidence: 99%